The sponge fauna of the Seno Magdalena and Puyuhuapi Fjord (Chile), with a description of two new species - BERTOLINO, MARCO; COSTA, GABRIELE; REBOA, ANNA; BAVESTRELLO, GIORGIO; PANSINI, MAURIZIO; BETTI, FEDERICO; BO, MARZIA; DANERI, GIOVANNI (Zootaxa, 2019)
The presence of fjords, islands and channels originating from glacial erosion and ice cap retreat, makes the Chilean benthic biodiversity difficult to explore and study. Our survey of this region allowed the identification of 29 Demospongiae species in total. Two of them are new to science and here described: Biemna lutea sp. nov., and Hamigera cleistochela sp. nov. Two species (Clathria (Clathria) microxa and Lissodendoryx (Ectyodoryx) patagonica,) are new for the region and the Chilean fjords. Lissodendoryx (Ectyodoryx) patagonica was found for the second time after the original description by Ridley & Dendy, 132 years ago. These results – considering the small number of species identified on the whole – are promising and confirm that the marine biodiversity of Chilean fjords is remarkable but not well known yet.